Penerapan Prinsip Akuntabilitas dalam Proses Administrasi Keuangan di Bank Muamalat KCP Rancaekek - Tia Junita Dewi; Gina Sakinah (Jurnal Riset Multidisiplin Edukasi, 2026)
Accountability is a fundamental principle in the financial management of Islamic banking institutions. The correct implementation of accountability is necessary to maintain public trust and ensure that operational activities comply with applicable regulations. The purpose of this research is to analyze the application of accountability principles in the financial management process at Bank Muamalat KCP Rancaekek. This research method uses a qualitative descriptive approach thru the utilization of secondary data, non-participant observation, and literature review. The research results show that the financial management process at Bank Muamalat KCP Rancaekek has been carried out in accordance with structured and documented procedures, thereby supporting the application of accountability principles. This study concludes that accountability in financial management is crucial for good governance in Islamic banking.